Transdermal Nitroglycerin as an Adjuvant to Patient-Controlled Morphine Analgesia after Total Knee Arthroplasty - Sharon Orbach-Zinger; Artium Lenchinsky; Lesley Paul-Kesslin; Steven Velks; Moses Salai; Leonid A Eidelman (Pain Research and Management)
BACKGROUND: Nitroglycerin (NTG) has been shown to be a useful adjunct for pain treatment without increasing adverse side effects. The effects of NTG on postoperative morphine consumption after knee replacement were evaluated.